Introduction: The Insanity Defense in the District of Columbia (Washington University Law Quarterly, 1973)
This Article provides an history of the evolution of various tests for an insanity defense in Washington, D.C., focusing on the most important case precedent in the field.
Keywords: Expert witnesses; Brawner v. United States; 417 F.2d 969 91972)